Die Schutzgottheiten des Raumes auf den Zaubermessern des Mittleren Reiches - Altenmüller, Hartwig (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
The investigation concerns the enigmatic signs incised on the magic ivories of the Middle Kingdom and the Second Intermediate Period. They represent tutelary deities mainly of the cardinal points protecting private houses and tombs against various demons and enemies. Apparently, they are forerunners of the symbols of the magical bricks of BD 151 from the New Kingdom.